Biotin-Thiamine Responsive Encephalopathy: Report of an Egyptian Family with a Novel SLC19A3 Mutation and Review of the Literature - Savasta, Salvatore; Bassanese, Francesco; Buschini, Chiara; Foiadelli, Thomas; Trabatti, Chiara; Efthymiou, Stephanie; Salpietro, Vincenzo; Houlden, Henry; Simoncelli, Annamaria; Marseglia, Gian Luigi (Journal of Pediatric Genetics, 2019)
Biotin-thiamine responsive basal ganglia disease (BTRBGD) is an autosomal recessive neurometabolic disorder with poor genotype-phenotype correlation, caused by mutations in the SLC19A3 gene on chromosome 2q36.6. The disease is characterized by three stages: stage 1 is a sub-acute encephalopathy often triggered by febrile illness; stage 2 is an acute encephalopathy with seizures, loss of motor function, developmental regression, dystonia, external ophthalmoplegia, dysphagia, and dysarthria; stage 3 is represented by chronic or slowly progressive encephalopathy. Clinical and biochemical findings, as well as the magnetic resonance imaging (MRI) pattern, resemble those of Leigh's syndrome, so that BTRBGD can be misdiagnosed as a mitochondrial encephalopathy.Here we report the clinical and radiological phenotypes of two siblings diagnosed with BTRBGD in which a novel SLC19A3 mutation (NM_025243.3: c.548C > T; p.Ala183Val) was found by whole exome sequencing (WES) of the family members.
Keywords: biotin-thiamine responsive basal ganglia disease; biotin; thiamine; encephalopathy; Leigh's syndrome